A case of genotype‐3b hepatitis C virus in which the whole genome was successfully analyzed using third‐generation nanopore sequencing. Issue 9 (13th June 2019) - Uchida, Yoshihito; Kouyama, Jun‐ichi; Naiki, Kayoko; Uemura, Hayato; Tsuji, Shohei; Sugawara, Kayoko; Nakao, Masamitsu; Motoya, Daisuke; Nakayama, Nobuaki; Imai, Yukinori; Tomiya, Tomoaki; Mochida, Satoshi
Abstract : A 42‐year‐old Chinese man with chronic hepatitis C virus (HCV) infection visited our hospital for antiviral therapy. The subgenotype could not be determined using the HCV GENOTYPE Primer Kit (Institute of Immunology, Tokyo, Japan), which can identify genotype 3a HCV exclusively among genotype 3 HCV. Thus, the whole‐genome sequence of HCV was analyzed using the MinION nanopore sequencer (Oxford Nanopore Technologies, Oxford, UK), a third‐generation single‐molecule sequencing platform. Consequently, a total of 9442 bases with a 73.6 mean depth, corresponding to the sequences between nt25 and PolyU/UC were determined (LC414155.2). The similarity analysis revealed that the obtained sequence was classified into genotype 3b HCV and showed nucleotide identities from 87.6% to 93.9% with those of 12 previously reported strains. Furthermore, possible resistance‐associated substitutions in non‐structural protein (NS)3, NS5A, and NS5B based on consensus sequences of 12 genotype 3b HCV strains, including NS5A‐Y93H and NS5B‐S282 T substitutions, were absent. In conclusion, the MinION nanopore sequencer is useful for analyzing the HCV genome, especially the genomes of genotype 3 HCV strains for which standardized real‐ time PCR methods for all subgenotypes have not been established.